2012
DOI: 10.1007/s12010-011-9513-7
|View full text |Cite
|
Sign up to set email alerts
|

ANCUT2, an Extracellular Cutinase from Aspergillus nidulans Induced by Olive Oil

Abstract: Cutinases are versatile carboxylic ester hydrolases with great potential in many biocatalytic processes, including biodiesel production. Genome sequence analysis of the model organism Aspergillus nidulans reveals four genes encoding putative cutinases. In this work, we purified and identified for the first time a cutinase (ANCUT2) produced by A. nidulans. ANCUT2 is a 29-kDa protein which consists of 255 amino acid residues. Comparison of the amino acid sequence of ANCUT2 with other microbial cutinase sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…Furthermore, due to the difficulty of assessing the enzymatic activity of cutinase using radiolabeled cutin as substrate (Purdy & Kolattukudy, 1973;Davies et al, 2000). It was decided to detect cutinase activity by simpler methods using native cutins as substrate (Castro-Ochoa et al, 2012), and 4-nitrophenyl esters as commercial substrates (Degani et al, 2006). Degani (2015) reported that cutinase activity increases according to the amount of cutin added to the culture media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to the difficulty of assessing the enzymatic activity of cutinase using radiolabeled cutin as substrate (Purdy & Kolattukudy, 1973;Davies et al, 2000). It was decided to detect cutinase activity by simpler methods using native cutins as substrate (Castro-Ochoa et al, 2012), and 4-nitrophenyl esters as commercial substrates (Degani et al, 2006). Degani (2015) reported that cutinase activity increases according to the amount of cutin added to the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…Cutinases (E.C 3.1.1.73) are extracellular and inducible enzymes which break down cutin, the major component of vegetal cuticle in higher plants, which is composed of esterified fatty acids (C16 or C18) (Castro-Ochoa et al, 2012). Cutinases are predominantly produced by phytopathogenic fungi with the ability to grow on cutin as sole carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple cutinase genes have been identified in each of the following fungal species: F. solani f. sp. pisi 9 , A. oryzae 10 , and Aspergillus nidulans 11,12 . The expression of these genes is induced by polyesters such as biodegradable plastics or the plant polyester suberin 5, 11 13 .…”
Section: Selection Of Suitable Amounts Of Carbon Pbsa Formentioning
confidence: 99%
“…CAK41954.1) and A. flavus (GenBank accession no. EED52785.1) at the C-terminal [5]. In addition, the first author also wishes to thank the Government of the Kingdom of Saudi Arabia for awarding the fellowship for doctoral research.…”
Section: Enzymatic Treatment Of Synthetic Polymersmentioning
confidence: 99%
“…Interestingly, this enzyme is also implicated in the pathogenicity of plant pathogenic fungi to break down plant cell walls releasing cutin monomers [4]. Cutinase belongs to the α/β hydroloase fold and serine esterase super-family with the classical Ser, His, and Asp triad [5,6].…”
Section: Introductionmentioning
confidence: 99%